The Impact of a Non-profit Market on Food Store Choice and Shopping Experience: A Community Case Study - Yao, Mengni; Hillier, Amy; Wall, Elizabeth; DiSantis, Katherine I. (Frontiers in Public Health, 2019)
Research evaluating the impact of new food stores in "food deserts" have reported limited impact on eating and health outcomes of residents who live nearby. Few studies have reported on shoppers' food store choices and experiences in these new stores. This study focused on residents' experience with a new nonprofit food market in Chester, PA and analyzes spatial patterns regarding who did and did not choose to shop at the new store. Phone surveys (n = 135) and in-person interviews (n = 13) were conducted with the primary food shopper for households living in Chester one year and two years, respectively, after the opening of a store. Participants who shopped at the new market reported positive experiences in regard to convenience, customer service, food quality and prices and believed that the new market had a positive impact on the community. But most participants had not shopped at the new market, citing many of the same factors in their decision to shop at supermarkets outside the city. Our findings underscore the need to combine new food retail strategies with community engagement and other interventions, such as in-store promotions and health education programs, to maximize the number of people who shop at new food outlets designed to improve access to healthful foods.